Coordinated investigation of summer time mid‐latitude descending E layer (Es) perturbations using Na lidar, ionosonde, and meteor wind radar observations over Logan, Utah (41.7°N, 111.8°W). Issue 4 (28th February 2013) - Yuan, Tao; Fish, C.; Sojka, J.; Rice, D.; Taylor, M. J.; Mitchell, N. J.
Abstract : [1] It is well known that there is a strong correlation between the formation of a descending sporadic E layer (Es ) and the occurrence of large upper atmospheric zonal wind shears, most likely driven by solar thermal tides and/or gravity waves. We present new results of Es perturbation events captured between 13 and 17 July 2011 (UT days 194–198) as part of a coordinated campaign using a wind/temperature Na lidar at Utah State University [41.7ºN, 111.8°W], and a Canadian Advanced Digital Ionosonde (CADI; Scientific Instrumentation Ltd., Saskatoon, Saskatchewan, Canada) and SkiYMet meteor wind radar, both located at nearby Bear Lake Observatory [41.9°N, 111.4°W]. During this period, the CADI detected strong descending Es on 2 days (195 and 197) when large modulations of the top‐side mesospheric Na layer occurred in synchronism with strong oscillations in the ionosonde E region echoes. A weakening in the descending E layer echoes was observed on the other 2 days (196 and 198) coincident with a large reduction in the zonal diurnal and semidiurnal amplitudes above 95 km. Both tidal components were found to have comparable contributions to the total zonal wind shear that was critical for Es formation and its downward propagation. Further investigation indicates that the weakening tidal amplitudes and the occurrence of the Es events were also influenced by a strong quasi‐two‐day period modulation, suggesting significant quasi‐two‐day wave (QTDW) interactions with the tides. Indeed, a nonlinear, wave‐wave interaction‐induced 16‐hour period child wave was also detected, with amplitude comparable to that of the prevailing tides. These interaction processes and their associated effects are consistent with earlier Thermosphere Ionosphere Mesosphere Electrodynamics General Circulation Model studies of nonlinear interactions between the migrating tidal waves and the QTDW and were probably responsible for the observed damping of the tidal amplitudes resulting in the disruption of the Es . Key Points: Es induces large perturbations of Na abundance in lower thermosphere Es weakening is coincident with weakening of zonal wind tides The damping of tidal amplitude is the result of interaction between PW and Tide